Activating Transcription Factor 6 Is Necessary and Sufficient for Alcoholic Fatty Liver Disease in Zebrafish - Howarth, Deanna L.; Lindtner, Claudia; Vacaru, Ana M.; Sachidanandam, Ravi; Tsedensodnom, Orkhontuya; Vasilkova, Taisa; Buettner, Christoph; Sadler, Kirsten C. (PLoS genetics, 2014)
Fatty liver disease (FLD) is characterized by lipid accumulation in hepatocytes and is accompanied by secretory pathway dysfunction, resulting in induction of the unfolded protein response (UPR). Activating transcription factor 6 (ATF6), one of three main UPR sensors, functions to both promote FLD during acute stress and reduce FLD during chronic stress. There is little mechanistic understanding of how ATF6, or any other UPR factor, regulates hepatic lipid metabolism to cause disease. We addressed this using zebrafish genetics and biochemical analyses and demonstrate that Atf6 is necessary and sufficient for FLD. atf6 transcription is significantly upregulated in the liver of zebrafish with alcoholic FLD and morpholino-mediated atf6 depletion significantly reduced steatosis incidence caused by alcohol. Moreover, overexpression of active, nuclear Atf6 (nAtf6) in hepatocytes caused FLD in the absence of stress. mRNA-Seq and qPCR analyses of livers from five day old nAtf6 transgenic larvae revealed upregulation of genes promoting glyceroneogenesis and fatty acid elongation, including fatty acid synthase (fasn), and nAtf6 overexpression in both zebrafish larvae and human hepatoma cells increased the incorporation of 14C-acetate into lipids. Srebp transcription factors are key regulators of lipogenic enzymes, but reducing Srebp activation by scap morpholino injection neither prevented FLD in nAtf6 transgenics nor synergized with atf6 knockdown to reduce alcohol-induced FLD. In contrast, fasn morpholino injection reduced FLD in nAtf6 transgenic larvae and synergistically interacted with atf6 to reduce alcoholic FLD. Thus, our data demonstrate that Atf6 is required for alcoholic FLD and epistatically interacts with fasn to cause this disease, suggesting triglyceride biogenesis as the mechanism of UPR induced FLD.